Exogenous N-Acetylcysteine alleviates heavy metal stress by promoting phenolic acids to support antioxidant defence systems in wheat roots - Colak, Nesrin; Torun, Hülya; Gruz, Jiri; Strnad, Miroslav; Ayaz, Faik Ahmet (Ecotoxicology and environmental safety, 2019)
N-acetylcysteine (N-Acetyl L-cysteine, NAC) is a thiol compound derived from the addition of the acetyl group to cysteine amino acid. NAC has been used as an antioxidant, free radical scavenger, and chelating agent for reducing the deleterious effects on plants of biotic and abiotic environmental stresses. It can also relieve heavy metal (HM) toxicity, although its alleviating mechanism remains unknown. In this study, we compared HM-stressed (Cu, Hg, Cd and Pb, 100 μM each) wheat seedlings without NAC treatment and in combination with NAC (1 mM). In comparison to HMs alone, NAC treatment in combination with HMs (Cu, Cd, Hg and Pb, respectively) stimulated root growth (1.1-, 1.5-, 10.5- and 1.9-fold), and significantly increased fresh (1.3-, 1.5-, 4.3- and 1.4-fold) and dry (1.2-, 1.5-, 2.5- and 1.2-fold) mass. Combination treatment also led to significant reductions in HM concentrations (1.3-, 1.4-, 4- and 1.1-fold, respectively). GSH (1.1 - 1.8-fold), TBARS (1.4 - 2.7-fold) and H2O2 (1.6 - 1.8-fold) contents in treatment with HMs alone were significantly mitigated by the NAC combination. Some of the antioxidant enzyme activities increased or reduced by some HM treatments alone were stimulated by a combination of NAC with HMs, or remained unchanged or changed only insignificantly, supported by the phenolic pool of the plant. Ferulic, p-comaric and syringic acids were the major phenolic acids (PAs) in the roots in free, ester, glycoside and ester-bound forms, and their concentrations were increased by HM treatments alone, in comparison to the control seedlings, while PAs concentrations were relatively reduced by NAC in combination with HMs. These results indicate that NAC can alleviate HM toxicity and improve the growth of HM-stressed wheat seedlings by coordinated induction of the phenolic pool and the antioxidant defence system.
Keywords: Triticum; oxidační stres; antioxidancia; semenáček; Acetylcysteine; látky reagující s kyselinou thiobarbiturovou; těžké kovy; acetylcystein; Thiobarbituric Acid Reactive Substances; pšenice; peroxid vodíku; látky znečišťující půdu; Hydroxybenzoates; Hydrogen Peroxide; Soil Pollutants; Antioxidants; Seedlings; hydroxybenzoáty; Metals, Heavy; Oxidative Stress